Perancangan Sistem Informasi Rekap Data Pasien Klinik Universitas Merdeka Madiun - Amadi, Dwi Nor; Prasetyo, Hendra Budi (JURNAL PILAR TEKNOLOGI : Jurnal Ilmiah Ilmu Ilmu Teknik, 2019)
Administration At the "Merdeka madiun" university clinic currently not well ordered and have not utilised IT technology, for it needs to build an information system that contains track records of patients who have done the examination or treatment at an independent "Merdeka madiun" university clinic. For that, we need to think about how to make information system of patient data recap at "Merdeka madiun" university clinic. So that traceable history of patient health and Built a Patient Data Recap at the "Merdeka madiun" university with an android and web-based opensource platform.